Molecular insights into de novo small-molecule recognition by an intron RNA structure - Tianshuo Liu; Ling Xu; Kevin Chung; Luke J. Sisto; Jimin Hwang; Chengxin Zhang; Michael C. Van Zandt; Anna Marie Pyle (Proceedings of the National Academy of Sciences, 2025)
Despite the promise of vastly expanding the druggable genome, rational design of RNA-targeting ligands remains challenging as it requires the rapid identification of hits and visualization of the resulting cocomplexes for guiding optimization. Here, we leveraged high-throughput screening, medicinal chemistry, and structural biology to identify a de novo splicing inhibitor against a large and highly folded fungal group I intron. High-resolution cryoEM structures of the intron in different liganded states not only reveal molecular interactions that rationalize experimental structure–activity relationship but also shed light on a unique strategy whereby RNA-associated metal ions and RNA conformation exhibit exceptional plasticity in response to small-molecule binding. This study reveals general principles that govern RNA–ligand recognition, the interplay between chemical bonding specificity, and dynamic responses within an RNA target.